Interest in a national research network in surgery in Switzerland (Swiss Medical Weekly, 2011)
BACKGROUND: Networks are known to improve performance and create synergies. A research network can provide a significant advantage for all parties involved in research in surgery by systematically tracking the outcome of a huge number of patients over a long period of time. The aim of the present study was to investigate the experiences of surgeons with respect to research activities, to evaluate the opinions of surgeons with regard to the development of a national network for research in the field of surgery in Switzerland and to obtain data on how such a network should be designed. METHODS: An anonymous postal survey of board-certified surgeons practising in Switzerland was conducted during summer 2007. The questionnaire included questions related to research activities, the desire to develop a national research network and the design and potential advantages of such a network. Qualitative analyses were performed using Mayring’s content analysis. RESULTS: A total of 337 out of 749 (45%) questionnaires were returned. In all, 156/337 (46.3%) surgeons were engaged in research activities. During the past five years, 212/337 (62.9%) of the participants had participated at least in one multi-centre study. Out of 337, 88 (26.1%) surgeons were members of an established research association in Switzerland. Interest in a national surgical research network was reported by 266 (78.9%) participants. The reported advantages were “power” (53.1%), “teamwork effects” (23.7%), “efficiency” (12.2%) and “quality aspects” (8.0%). The most frequently named design proposal was based on a clinic for coordinating research, while the younger participants also suggested a web-based platform. CONCLUSIONS: Due to the significant interest of participants, the establishment of a national research network should be considered. An established clinic for coordinating research alongside an additional web-based platform to target young surgeons could function as an umbrella organisation.